Alopecia - Ahmad, Muhammad (IntechOpen, 2018)
Being the editor of the book Alopecia, I feel delighted to work with the world-leading publisher IntechOpen Publisher. The current book has chapters emphasizing a variety of alopecias. The administration of newer drugs may treat hair loss by a variety of mechanisms. All the clinical variants of alopecias are discussed in detail. The book will help dermatologists, students, hair transplant surgeons, and physicians related to hair loss problems, giving them the opportunity to understand basic pathophysiological, clinical, and medical management options. The basic idea of the book is to diagnose alopecia correctly.